MORALITAS TOKOH DALAM CERITA ANAK â€œEINE WOCHE VOLLER SAMSTAGEâ€ KARYA PAUL MAAR - RIZKY ARTHANTI, LANNY (IDENTITAET, 2016)
Morality by Poepoprodjo (1998: 118) is a quality of human’s behavior, which indicated that the behavior is good or bad. In the children’s story “Eine Woche voller Samstage” by Paul Maar have many morality lessons for the readers. The formulation of the problems is : How the morality in the children’s story “Eine Woche voller Samstage” by Paul Maar? And the purpose of the research is to identify the morality in the  story. This research is the qualitative research. Then to analyse used the Theorie by Poespoprodjo called determinants of morality, consist of : (1) The self act, (2) Motif, (3) Condition. The techniqueanalyse consist of : (1) reading and understanding the story, (2) Analyse the character in the story with Charracteranalyse Method. (3) The Datas classified in the words, sentences, and frase, (4) Make any conclusion from the descriptions result. The descriptions results in the every character in this children’s story have good morality and bad morality. Keywords : Morality, story, Maar.